Dyslipidemia in Type 2 Diabetes mellitus (Journal of Pathology of Nepal, 2017)
Background: In type 2 diabetes mellitus lipid abnormalities are very common and is associated with increased risk of cardiovascular diseases.  This study was conducted to find association of type 2 diabetes and dyslipidemia.Materials and Methods: This cross-sectional study was conducted at KISTMCTH. All the necessary data of patient with type 2 diabetes in the period between December 2016 and May 2017 were studied.Results: Out of 199 patients with diabetes mellitus 30.7% had total cholesterol >200 mg/dl, 64.4% had elevated low density lipoprotein, 53.77% patient had elevated triglyceride and 64% patients had low high density lipoprotein level. Cholesterol showed significant correlation with triglyceride (P